The Services Quality Influence the Satisfaction of SMEs and fees Paid on Non-Audit Services Provided by Small and Medium Practitioners (SMPS) - Yuvaraj, Ganesan; Hasnah, Haron; Ishak, Ismail (Universiti Malaysia Pahang, 2017)

(untitled)
It is an undeniable fact that Small Medium Enterprises (SMEs) play an essential role in the growth of the economy of Malaysia. Although SMEs form the majority of the total number of registered companies in Malaysia, its contribution to the country’s gross domestic product (GDP) is still not significant as compared to SMEs in other countries. Generally, SMEs are facing many challenges and barriers such as lack of managerial capabilities, shortage in financing and human resource. This forced SMEs to find the expertise from an external party such as an accountant in term of non-audit services (NAS) to overcome their challenges. As an external accountant is the first choice for SMEs to seek the advices, it is essential to study the service quality of external accountant who providing the NAS to SMEs and the relationship with satisfaction and non-audit fees. A total 106 usable responses were used in the analysis and found that from the five dimensions of service quality only four dimensions (namely tangible, assurance, responsiveness and reliability) has a significant relationship with satisfaction. Meanwhile, only assurance, responsiveness and reliability significantly affect the level of nonaudit fees paid. The finding helps external accountant to strategize their services in order to satisfying their customer and determined the level of fees would like to charge. Overall, this paper draws attention to the importance services quality of NAS in enhancing the survival of the SMEs